(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Acute urinary retention (AUR) is an important public health issue in older male population with benign prostatic hyperplasia (BPH). Various risk factors are associated with increased incidence of AUR among patients with BPH being managed conservatively. Method: A retrospective analysis was performed AUR with BPH among patients in Shree Birendra Hospital (SBH), Chhauni, Kathmandu, Nepal for a period of one year. Study variables included patient age, serum prostate specific antigen (PSA), prostate volume, history of AUR, smoking, diabetes mellitus, hypertension, cardiovascular disease, and other comorbid diseases. The SPSS was used for data analysis, X2 test to find out the association and a p<0.05 considered statistically significant. The study was approved from the ethical committee. Result: Total 110 patients (out of 182 BPH) had AUR, an incidence of 60.9% (110 out of 182), with a mean (SD) age of 67.41±7.1 (p<0.05). Patients with AUR had larger mean prostate volume. There were 38(34.54 %) patients with AUR having PSA >4.5 ng/mL (p<0.001). More number of patients with AUR had diabetes mellitus and smoker (p<0.001). Consumption of alcohol, hypertension and cardiac disease were not significantly associated with AUR (p>0.05). Conclusion: Our study showed that increasing age, high prostate volume, high serum PSA, diabetes and smoking had increased incidence of AUR among patients with BPH.